Electrophysiological Measures of Tactile and Auditory Processing in Children With Autism Spectrum Disorder - Kadlaskar, Girija; Bergmann, Sophia; McNally Keehn, Rebecca; Seidl, Amanda; Keehn, Brandon (Frontiers in Human Neuroscience, 2021)
Behavioral differences in responding to tactile and auditory stimuli are widely reported in individuals with autism spectrum disorder (ASD). However, the neural mechanisms underlying distinct tactile and auditory reactivity patterns in ASD remain unclear with theories implicating differences in both perceptual and attentional processes. The current study sought to investigate (1) the neural indices of early perceptual and later attentional factors underlying tactile and auditory processing in children with and without ASD, and (2) the relationship between neural indices of tactile and auditory processing and ASD symptomatology. Participants included 14, 6- to 12-year-olds with ASD and 14 age- and non-verbal IQ matched typically developing (TD) children. Children participated in an event-related potential (ERP) oddball paradigm during which they watched a silent video while being presented with tactile and auditory stimuli (i.e., 80% standard speech sound /a/; 10% oddball speech sound /i/; 10% novel vibrotactile stimuli on the fingertip with standard speech sound /a/). Children’s early and later ERP responses to tactile (P1 and N2) and auditory stimuli (P1, P3a, and P3b) were examined. Non-parametric analyses showed that children with ASD displayed differences in early perceptual processing of auditory (i.e., lower amplitudes at central region of interest), but not tactile, stimuli. Analysis of later attentional components did not show differences in response to tactile and auditory stimuli in the ASD and TD groups. Together, these results suggest that differences in auditory responsivity patterns could be related to perceptual factors in children with ASD. However, despite differences in caregiver-reported sensory measures, children with ASD did not differ in their neural reactivity to infrequent touch-speech stimuli compared to TD children. Nevertheless, correlational analyses confirmed that inter-individual differences in neural responsivity to tactile and auditory stimuli were related to social skills in all children. Finally, we discuss how the paradigm and stimulus type used in the current study may have impacted our results. These findings have implications for everyday life, where individual differences in responding to tactile and auditory stimuli may impact social functioning.